Pharmacy students’ knowledge of psychotropic medicines and their attitude towards providing pharmaceutical care to patients with anxiety in Nigeria (2022)
Background: Healthcare professionals, such as pharmacists, play critical roles in the management of mental disorders by assessing the potential for adverse reactions, providing medication counseling, and medication review optimize treatment regimens. Objectives: This study aims to assess the knowledge of pharmacy students in a Nigerian university regarding psychotropic medicines and their attitude towards providing pharmaceutical care to patients with anxiety. Method: A cross-sectional web-based survey was conducted in May 2021 among fourth- and fifth-year pharmacy students in a Nigerian university. The data were summarized using descriptive statistics, such as frequencies and percentages. Chi square was utilized to examine the association between the demographic characteristics and the respondents' overall knowledge and attitude. Results: The response rate was 85%, as 126 responses were received. About half of the respondents 69 (54.8%) reported that they have received training on psychotropic medicines and 9 (9.1%) have been previously diagnosed with anxiety disorders. Only 53 (42.1%) and 71 (56.3%) of our respondents knew that escitalopram and alprazolam are categorized as anxiolytics respectively. Most respondents would like to talk to patients with anxiety about their medications 110 (87.3%), attend training on pharmaceutical care for patients with anxiety 103 (81.7%), and obtain a medication history for people with anxiety 113 (89.7%). Ninety-four (74.6%) pharmacy students would like to suggest prescription medication for a patient with anxiety and only 88 (69.8%) would like to correct any errors in prescription in any anxiety cases. Our findings also revealed that there is a significant association between the students’ attitude and year of study (p=0.038) and previous training on psychotropic medicines (p=0.004). Conclusion: Findings from this study suggested that participants require improved knowledge and training of psychotropic medicines.